Depression, anxiety and change in eating habits during the COVID-19 pandemic in Brazilian university students - Marcus Verly-Miguel; Claudia de Souza Lopes; Jade Veloso Freitas; Magno Conceição Garcia; Marcio Candeias Marques; Vitor Barreto Paravidino; Rosely Sichieri (PLoS ONE, 2025)
This cross-sectional study aims to evaluate the association between anxiety and depression with changes in the consumption of hyperpalatable foods and meal patterns in a sample of 771 Brazilian university students during the social isolation period in the COVID-19 pandemic. More than half of the subjects self-reported clinically significant symptoms of anxiety (53.8%) and depression (62.5%), with 47.6% having both. Most individuals who showed increased consumption of hyperpalatable foods were also part of the group that reported clinically significant symptoms of anxiety or depression. Statistical analysis was performed using exploratory structural equations. The latent variable “symptoms of anxiety and depression” was created using the anxiety and depression scores. Symptoms of anxiety and depression had a positive correlation with the increased consumption of hyperpalatable foods and meal substitution (standardized coefficient = 0.212), after analysing their total direct and indirect effects. It was concluded that higher scores of anxiety and depression negatively affects the eating habits of university students.